Effects of two types of repetitive transcranial magnetic stimulation on brain network in Parkinson’s disease - Shuo Liu; Shuo Yang; Chen Wang; Jiarui Li; Lei Wang (npj Parkinson's Disease)
Abstract Intermittent theta burst stimulation (iTBS) may have higher efficiency and stronger excitatory effects compared to conventional high-frequency repetitive transcranial magnetic stimulation (HF-rTMS). To evaluate the therapeutic effects of the two modalities, we compared the differences in spatiotemporal variability of electroencephalography (EEG) microstate-based brain networks between 51 PD patients and 21 healthy controls. The 51 PD patients were randomly assigned to either iTBS or 10Hz-rTMS groups to compare pre- and post-treatment clinical assessment results and spatiotemporal variability changes. Baseline measurements showed significant differences in spatiotemporal variability between PD patients and healthy controls, with certain brain regions demonstrating significant correlations between spatiotemporal variability and clinical assessment results. Both treatment groups exhibited significant improvements in all clinical outcomes compared to baseline. The iTBS group showed post-treatment changes involving more brain regions in spatiotemporal variability. This study demonstrates that compared to 10Hz-rTMS, iTBS can reduce treatment time while providing superior improvement in functional brain connectivity for PD patients.